A Study On The Effectiveness Of Hypnocaring Technique In Managing Post-Cesarean Section Pain (At Syekh Yusuf Gowa General Hospital) - Nurhijrani N; Sartika S (Jurnal EduHealth, 2024)
The hypnocaring technique is a non-pharmacological approach that utilizes therapeutic communication between nurses and clients. Through the use of affirmations and positive suggestions, this technique aims to enhance motivation and empower patients in their healing process. With a focus on empathetic interpersonal relationships, hypnocaring has the potential to be an effective solution for addressing the challenges often faced by post-sectio caesarea patients, namely pain and post-operative anxiety. This study aims to describe the implementation of the hypnocaring technique and evaluate its impact on reducing pain and anxiety in clients, as well as assess its contribution to the quality of care received by patients. The study employs a qualitative research method with a participant observation approach, where the researcher is directly involved in the observed activities to gain deeper data insights. Participant observation is a qualitative research technique that allows the researcher to interact with study subjects in their natural environment, enabling them to understand the patterns of social interaction, behavior, and the meanings behind the observed actions. The findings reveal that overall, the use of hypnocaring techniques at Syekh Yusuf Regional Hospital in Gowa shows great potential in helping alleviate pain and anxiety in post-cesarean section clients. Despite some inhibiting factors, supporting factors such as the support from healthcare professionals, the willingness of clients, and a conducive environment can maximize the application of this technique. It is recommended that the management of Syekh Yusuf Regional Hospital provide special training for nurses regarding the implementation of the hypnocaring technique. This training is crucial to ensure that nurses have the adequate skills to apply the technique optimally.